Anti-VEGF (vascular endothelial growth factor) intraocular sustained-release implant with high drug loading capacity and preparation method thereof
By mixing anti-VEGF active ingredients with water-insoluble biodegradable sustained release polymers and preparing anti-VEGF intraocular sustained release implants using hot melt extrusion mechanism, frequent injections and complications of existing anti-VEGF intraocular injection therapy are solved. The problem of long-term sustained release and high bioavailability has been achieved, reducing the risk of complications.
Patent Information
- Application Number
- CN202411257720.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-27
AI Technical Summary
The existing anti-VEGF intraocular injection therapy requires frequent injection due to the short half-life of the drug and the unresponsiveness to some patients, resulting in complications such as eye inflammation, increased intraocular pressure, decreased vision and retinal shedding, and increased heart The risk of cerebrovascular events is urgently needed in clinical practice.
Using a high drug load anti-VEGF intraocular sustained release implant preparation method, the uniform dispersion of the drug and the use of hot melt extrusion mechanism is achieved by mixing the anti-VEGF active ingredients with water-insoluble biodegradable sustained release polymer. The sustained release avoids contact between raw materials and solvents, improves biocompatibility, and regulates the drug release time by regulating the polymer species.
Achieve long-term sustained release of drugs, reduce the number of surgeries and complications, improve the bioavailability of drugs and patient compliance, avoid the ocular drug delivery barrier, provide excellent sustained release effect, and in vitro release time It can reach several days to dozens of days.
Smart Images

Figure CN119185164A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of medical technology, and particularly relates to an anti-VEGF intraocular sustained-release implant with a high drug loading and a preparation method thereof. Background Art
[0002] At present, the occurrence and development of many eye diseases, especially fundus diseases such as wet age-related macular degeneration, proliferative diabetic retinopathy, retinopathy of prematurity, sickle cell retinopathy and retinal vascular occlusion are closely related to vascular endothelial growth factor (VEGF). Common treatments currently include intravitreal injection of anti-VEGF or steroid drugs, panretinal laser photocoagulation and other clinical therapies. Although laser photocoagulation has been proven to effectively inhibit neovascularization in clinical trials, it may induce decreased vision, visual field constriction and decreased night vision due to laser-induced retinal tissue damage. Compared with photocoagulation therapy, intraocular injection of anti-VEGF drugs has become the first-line treatment for the above-mentioned related eye diseases.
[0003] Currently, anti-VEGF drugs used in clinical practice include: ranibizumab, bevacizumab, aflibercept and conbercept, but most of them require frequent intraocular injections to achieve therapeutic effects due to factors such as short half-life, limited duration and no response in some patients, which may cause complications such as eye inflammation, increased intraocular pressure, conjunctival hemorrhage, decreased vision and retinal detachment in patients, and even increase the risk of cardiovascular and cerebrovascular events, bringing a heavy treatment burden to patients and medical staff. Therefore, a new type of ocular sustained-release anti-VEGF drug delivery system is urgently needed for the treatment of RNV-related diseases.
[0004] Intraocular implants are a type of drug delivery system that is surgically implanted or introduced into the target site via a special device. In recent years, sustained-release implants made from water-insoluble biodegradable sustained-release polymers such as polylactic acid, polylactic-co-glycolic acid, and polycaprolactone and drugs have received increasing attention in clinical research. Summary of the invention
[0006] In view of this, the object of the present invention is to provide an anti-VEGF intraocular sustained-release implant with a high drug loading and a preparation method thereof. The anti-VEGF intraocular sustained-release implant prepared by the present invention has a drug loading of up to 60% and has a relatively excellent sustained-release effect.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] The present invention provides a method for preparing an anti-VEGF intraocular sustained-release implant with a high drug loading, comprising the following steps:
[0009] (1) crushing and sieving the anti-VEGF active ingredient to obtain an average particle size within a range of 70 to 125 μm;
[0010] (2) crushing and sieving the water-insoluble biodegradable sustained-release polymer to a mean particle size within a range of 70 to 125 μm;
[0011] (3) uniformly mixing the crushed and sieved anti-VEGF active ingredient with the water-insoluble biodegradable sustained-release polymer to obtain a premixed powder;
[0012] (4) Setting the temperature of the hot melt extruder to 90-150° C., setting the screw speed to 15-30 r / min, and installing a 0.3-1.0 mm diameter die;
[0013] (5) After the hot melt extruder is preheated to the set temperature, the premixed powder of step (3) is fed into the feed port, and the timing is started after all the powder enters the machine;
[0014] (6) After timing for 5 to 30 minutes, start extrusion and collect the middle 50 to 150 cm of the implant.
[0015] Based on the above technical solution, further, the anti-VEGF active ingredient in step (1) is one or a combination of two or more of nintedanib ethanesulfonate, nintedanib and voronib.
[0016] Based on the above technical solution, further, the water-insoluble biodegradable sustained-release polymer in step (2) is one or a combination of two or more of polylactic acid, polylactic acid-glycolic acid copolymer, and polycaprolactone.
[0017] Based on the above technical solution, further, the polylactic acid is one of acid-terminated and ester-terminated, and the intrinsic viscosity of the polylactic acid is one of 0.16-0.24 dl / g, 0.25-0.35 dl / g and 0.80-1.20 dl / g;
[0018] The polylactic acid-glycolic acid copolymer is one of acid-terminated and ester-terminated; the intrinsic viscosity of the polylactic acid-glycolic acid copolymer is 0.16-0.24 dl / g or 0.70-0.90 dl / g; the molar ratio of lactic acid to glycolic acid in the polylactic acid-glycolic acid copolymer is 75:25 or 50:50; the intrinsic viscosity of the polycaprolactone is 1.13-1.38 dl / g.
[0019] Based on the above technical solution, further, in step (3), the mass ratio of the anti-VEGF active ingredient to the water-insoluble biodegradable sustained-release polymer is 4:6 to 7:3, preferably 5:5 to 6:4.
[0020] Based on the above technical solution, further, in step (3), the mixing time is 5 to 30 minutes, preferably 8 to 12 minutes.
[0021] Based on the above technical solution, further, the temperature of the hot melt extruder in step (4) is set to 100-140°C, preferably 120-140°C; the screw speed is 15-25r / min, preferably 17-23r / min; the mold diameter is 0.3-0.7mm, preferably 0.4-0.6mm.
[0022] Based on the above technical solution, further, the timing in step (6) is 10 to 30 minutes, preferably 15 to 25 minutes.
[0023] The present invention also provides an anti-VEGF intraocular sustained-release implant prepared by the above preparation method.
[0024] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0025] 1) The present invention adopts a small hot-melt extrusion device to prepare the implant, and only 4g of material is needed for extrusion, which has a great advantage for small-scale research and development of expensive materials; by controlling parameters such as screw speed and extrusion temperature, the material can be evenly dispersed, and then the target shape preparation can be obtained by extrusion through a mold. This method avoids the contact between raw materials and solvents, thereby improving the biocompatibility of the preparation, and is easy to scale up and transform, and has a good industrial prospect;
[0026] 2) The in vitro sustained release time of the active ingredient in the implant of the present invention can be effectively adjusted by changing the type of the water-insoluble biodegradable sustained-release polymer;
[0027] 3) The implant of the present invention can directly achieve sustained release and continuous drug delivery at the target site in the eye, avoiding many eye drug delivery barriers, greatly improving the bioavailability of the drug, and only requires one surgery for implantation for the entire course of treatment, and does not need to be removed later, so it has good safety, reduces the risk of complications, and improves patient compliance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The extrusion expansion value of the implant prepared at different hot melt extruder temperatures described in Example 1;
[0029] Figure 2 The extrusion expansion value of the implant prepared at different screw speeds described in Example 2;
[0030] Figure 3 The extrusion expansion values of the implants prepared at different timing times as described in Example 3;
[0031] Figure 4The in vitro release curves of the implants described in Examples 4, 5 and 6 are shown;
[0032] Figure 5 The in vitro release curves of the implants described in Examples 7 and 8;
[0033] Figure 6 The in vitro release curves of the implants described in Examples 9 and 10;
[0034] Figure 7 This is the in vitro release curve of the implant described in Example 11;
[0035] Figure 8 The in vitro release curve fitting of the implant described in Example 10, wherein A is a zero-order equation, B is a first-order equation, C is a Higuchi equation, and D is a Ritger-Peppas equation;
[0036] Fig. 9 The scanning electron microscopy morphology of the implant described in Example 10 at different time points of in vitro release. DETAILED DESCRIPTION
[0037] The present invention is further described below by means of specific examples, including but not limited to these.
[0038] Example 1
[0039] 3 g of the active ingredient (nintedanib ethanesulfonate) after crushing and sieving (average particle size value of 70-125 μm) was preliminarily mixed with 2 g of a water-insoluble biodegradable sustained-release polymer (polylactic acid-glycolic acid copolymer, ester-terminated, intrinsic viscosity of 0.16-0.24 dl / g, lactic acid: glycolic acid = 75:25) for 10 minutes to obtain a premixed powder; the hot melt extruder (HAAKE CTW, MinilabⅡ hot melt extruder, Thermo Fisher Scientific, USA) was set at 90-150°C and the screw speed was 20 r / min. After preheating to the set temperature, the premixed powder was put in, and the timing was started for 20 minutes before extrusion through a 0.5 mm diameter die. The implant with a length of 50-150 cm in the middle was collected, and the diameter of 10 random positions of the implant was measured using a spiral micrometer, and the extrusion expansion value B was calculated. The calculation formula is as follows:
[0040] B = Actual implant diameter / mold diameter.
[0041] The results are as follows Figure 1 As shown by Figure 1It can be seen that when other parameters are fixed, as the temperature in the hot melt extruder increases, the raw and auxiliary materials in the machine gradually change from viscous to thin, and the torque gradually decreases, and the implant extrusion expansion value B is constantly approaching 1. When the hot melt extrusion temperature reaches above 150℃, the material is too thin and the machine torque is too low, so it cannot be extruded. Therefore, the hot melt extrusion temperature is set to 140℃.
[0042] Example 2
[0043] 3 g of the active ingredient (nintedanib ethanesulfonate) that was crushed and sieved (average particle size of 70-125 μm) was preliminarily mixed with 2 g of a water-insoluble biodegradable sustained-release polymer (polylactic acid-glycolic acid copolymer, ester-terminated, with an intrinsic viscosity of 0.16-0.24 dl / g, lactic acid:glycolic acid = 75:25) for 10 min to obtain a premixed powder; the temperature of the hot melt extruder was set to 140°C, and the screw speed was set to 15-30 r / min, respectively. After preheating to the set temperature, the premixed powder was added, and the timing was started 20 minutes later, and it was extruded through a 0.5 mm diameter die, and the implant with a length of 50-150 cm in the middle was collected. The diameter of 10 random positions of the implant was measured using a spiral micrometer, and the extrusion expansion value B was calculated.
[0044] The results are as follows Figure 2 As shown by Figure 2 It can be seen that when other parameters are fixed, as the screw speed decreases, the extrusion expansion value of the implant also decreases, and this phenomenon is more obvious at a high temperature of 140°C. However, the screw speed will also affect the extrusion speed of the implant. The slower the screw speed, the slower the implant is extruded from the hot melt extruder. Therefore, the screw speed of the hot melt extruder is determined to be 20r / min.
[0045] Example 3
[0046] 3 g of the active ingredient (nintedanib ethanesulfonate) that was crushed and sieved (average particle size of 70-125 μm) was preliminarily mixed with 2 g of a water-insoluble biodegradable sustained-release polymer (polylactic acid-glycolic acid copolymer, ester-terminated, with an intrinsic viscosity of 0.16-0.24 dl / g, lactic acid:glycolic acid = 75:25) for 10 min to obtain a premixed powder; the temperature of the hot melt extruder was set to 140°C and the screw speed was set to 20 r / min. After preheating to the set temperature, the premixed powder was put in and extruded through a 0.5 mm diameter die 5 to 30 minutes after the timing was started. The implants with a length of 50 to 150 cm in the middle were collected, and the diameters of 10 random positions of the implants were measured using a spiral micrometer, and the extrusion expansion value B was calculated.
[0047] The results are as follows Figure 3 As shown by Figure 3It can be seen that when other parameters are fixed, the extrusion expansion value B of the obtained implant does not change significantly with the change of the hot melt extruder cycle time. When the cycle time is 20 minutes, the B value is closest to 1. Therefore, the hot melt extrusion cycle time is determined to be 20 minutes.
[0048] Example 4
[0049] After determining the specific parameters of the process and hot-melt extrusion, the in vitro release time of the implants prepared using the active ingredient nintedanib ethanesulfonate did not exceed 7 days. This was considered to be caused by its hydrophilic ethanesulfonate group, so another active ingredient, nintedanib, was used for subsequent experiments.
[0050] 3 g of the active ingredient (nintedanib) that was crushed and sieved (average particle size of 70-125 μm) was preliminarily mixed with 2 g of a water-insoluble biodegradable sustained-release polymer (polylactic acid, acid-terminated, with an intrinsic viscosity of 0.16-0.24 dl / g) for 10 minutes to obtain a premixed powder; the hot melt extruder temperature was set to 140°C, the screw speed was set to 20 r / min, and the premixed powder was added after preheating to the set temperature. After the timing was started for 20 minutes, it was extruded through a 0.5 mm diameter die, and the implant with a length of 50-150 cm in the middle was collected.
[0051] Implants with a cut length of about 7 mm were placed at 37±0.5°C in 4 mL of 0.01 M (pH 7.4) PBS buffer containing 0.5% SDS for in vitro release. All release media were removed at a fixed time and replaced with an equal amount of fresh media. The drug content in the release medium was determined using an ultra-high performance liquid chromatograph (chromatographic column with octadecyl bonded silica as filler) (mobile phase: methanol: water + 0.05% triethylamine = 68:32, pH adjusted to 5.0; flow rate 0.20 mL / min; detection wavelength: 391 nm; detection temperature: 30°C; injection volume: 10 μL), and the cumulative release percentage of the theoretical content was calculated.
[0052] The in vitro release of the obtained implants was as follows Figure 4 As shown by Figure 4 It can be seen that the implant has a certain sustained-release effect, and the in vitro release time is relatively short.
[0053] Example 5
[0054] 3 g of the active ingredient (nintedanib) that was crushed and sieved (average particle size of 70-125 μm) was preliminarily mixed with 2 g of a water-insoluble biodegradable sustained-release polymer (polylactic acid, ester-terminated, with an intrinsic viscosity of 0.25-0.35 dl / g) for 10 minutes to obtain a premixed powder; the hot melt extruder temperature was set to 140°C and the screw speed was set to 20 r / min, and the premixed powder was added after preheating to the set temperature. After the timing was started for 20 minutes, it was extruded through a 0.5 mm diameter die, and the implant with a length of 50-150 cm in the middle was collected.
[0055] Implants with a cut length of about 7 mm were placed at 37±0.5°C in 4 mL of 0.01 M (pH 7.4) PBS buffer containing 0.5% SDS for in vitro release. All release media were removed at fixed time points and replaced with an equal amount of fresh media. The drug content in the release media was determined using an ultra-high performance liquid chromatograph, and the cumulative release percentage of the theoretical content was calculated.
[0056] The in vitro release of the obtained implants was as follows Figure 4 As shown by Figure 4 It can be seen that the implant has a relatively excellent sustained-release effect, and the in vitro release time can reach more than 10 days.
[0057] Example 6
[0058] 3 g of the active ingredient (nintedanib) that was crushed and sieved (average particle size of 70-125 μm) was preliminarily mixed with 2 g of a water-insoluble biodegradable sustained-release polymer (polylactic acid, ester-terminated, with an intrinsic viscosity of 0.80-1.20 dl / g) for 10 minutes to obtain a premixed powder; the hot melt extruder temperature was set to 140°C, the screw speed was set to 20 r / min, and the premixed powder was added after preheating to the set temperature. After the timing was started for 20 minutes, it was extruded through a 0.5 mm diameter die, and the implant with a length of 50-150 cm in the middle was collected.
[0059] Implants with a cut length of about 7 mm were placed at 37±0.5°C in 4 mL of 0.01 M (pH 7.4) PBS buffer containing 0.5% SDS for in vitro release. All release media were removed at fixed time points and replaced with an equal amount of fresh media. The drug content in the release media was determined using an ultra-high performance liquid chromatograph, and the cumulative release percentage of the theoretical content was calculated.
[0060] The in vitro release of the obtained implants was as follows Figure 4 As shown by Figure 4 It can be seen that the implant has a certain sustained-release effect and the in vitro release time is relatively long.
[0061] Example 7
[0062] 3 g of the active ingredient (nintedanib) that was crushed and sieved (average particle size of 70-125 μm) was preliminarily mixed with 2 g of a water-insoluble biodegradable sustained-release polymer (polylactic acid-glycolic acid copolymer, ester-terminated, with an intrinsic viscosity of 0.16-0.24 dl / g, lactic acid:glycolic acid = 75:25) for 10 minutes to obtain a premixed powder; the hot melt extruder temperature was set to 140°C and the screw speed was set to 20 r / min, and the premixed powder was added after preheating to the set temperature. After the timing was started for 20 minutes, it was extruded through a 0.5 mm diameter die, and the implant with a length of 50-150 cm in the middle was collected.
[0063] Implants with a cut length of about 7 mm were placed at 37±0.5°C in 4 mL of 0.01 M (pH 7.4) PBS buffer containing 0.5% SDS for in vitro release. All release media were removed at fixed time points and replaced with an equal amount of fresh media. The drug content in the release media was determined using an ultra-high performance liquid chromatograph, and the cumulative release percentage of the theoretical content was calculated.
[0064] The in vitro release of the obtained implants was as follows Figure 5 As shown by Figure 5 It can be seen that the implant has a sustained release effect, and the in vitro release time can reach more than 30 days.
[0065] Example 8
[0066] 3 g of the active ingredient (nintedanib) that was crushed and sieved (average particle size of 70-125 μm) was preliminarily mixed with 2 g of a water-insoluble biodegradable sustained-release polymer (polylactic acid-glycolic acid copolymer, ester-terminated, with an intrinsic viscosity of 0.70-0.90 dl / g, lactic acid:glycolic acid=75:25) for 10 minutes to obtain a premixed powder; the hot melt extruder temperature was set to 140°C and the screw speed was set to 20 r / min, and the premixed powder was added after preheating to the set temperature. After the timing was started for 20 minutes, it was extruded through a 0.5 mm diameter die, and the implant with a length of 50-150 cm in the middle was collected.
[0067] Implants with a cut length of about 7 mm were placed at 37±0.5°C in 4 mL of 0.01 M (pH 7.4) PBS buffer containing 0.5% SDS for in vitro release. All release media were removed at fixed time points and replaced with an equal amount of fresh media. The drug content in the release media was determined using an ultra-high performance liquid chromatograph, and the cumulative release percentage of the theoretical content was calculated.
[0068] The in vitro release of the obtained implants was as follows Figure 5 As shown by Figure 5 It can be seen that the implant has a certain sustained-release effect, and the in vitro release time can reach more than 14 days.
[0069] Example 9
[0070] 3 g of the active ingredient (nintedanib) that was crushed and sieved (average particle size of 70-125 μm) was preliminarily mixed with 2 g of a water-insoluble biodegradable sustained-release polymer (polylactic acid-glycolic acid copolymer, acid-terminated, with an intrinsic viscosity of 0.16-0.24 dl / g, lactic acid:glycolic acid=50:50) for 10 minutes to obtain a premixed powder; the hot melt extruder temperature was set to 140°C and the screw speed was set to 20 r / min, and the premixed powder was added after preheating to the set temperature. After the timing was started for 20 minutes, it was extruded through a 0.5 mm diameter die, and the implant with a length of 50-150 cm in the middle was collected.
[0071] Implants with a cut length of about 7 mm were placed at 37±0.5°C in 4 mL of 0.01 M (pH 7.4) PBS buffer containing 0.5% SDS for in vitro release. All release media were removed at fixed time points and replaced with an equal amount of fresh media. The drug content in the release media was determined using an ultra-high performance liquid chromatograph, and the cumulative release percentage of the theoretical content was calculated.
[0072] The in vitro release of the obtained implants was as follows Figure 6 As shown by Figure 6 It can be seen that the implant only has a certain sustained-release effect, and the in vitro release time is less than 7 days.
[0073] Example 10
[0074] 3 g of the active ingredient (nintedanib) that was crushed and sieved (average particle size of 70-125 μm) was preliminarily mixed with 2 g of a water-insoluble biodegradable sustained-release polymer (polylactic acid-glycolic acid copolymer, ester-terminated, with an intrinsic viscosity of 0.16-0.24 dl / g, lactic acid:glycolic acid=50:50) for 10 minutes to obtain a premixed powder; the hot melt extruder temperature was set to 140°C and the screw speed was set to 20 r / min, and the premixed powder was added after preheating to the set temperature. After the timing was started for 20 minutes, it was extruded through a 0.5 mm diameter die, and the implant with a length of 50-150 cm in the middle was collected.
[0075] Implants with a cut length of about 7 mm were placed at 37±0.5°C in 4 mL of 0.01 M (pH 7.4) PBS buffer containing 0.5% SDS for in vitro release. All release media were removed at fixed time points and replaced with an equal amount of fresh media. The drug content in the release media was determined using an ultra-high performance liquid chromatograph, and the cumulative release percentage of the theoretical content was calculated.
[0076] The in vitro release of the obtained implants was as follows Figure 6 As shown by Figure 6It can be seen that the implant has a very excellent sustained-release effect, and the in vitro release time can reach more than 30 days.
[0077] Embodiment 11
[0078] 3 g of the active ingredient (nintedanib) that was crushed and sieved (average particle size of 70-125 μm) was preliminarily mixed with 2 g of a water-insoluble biodegradable sustained-release polymer (polycaprolactone, with an intrinsic viscosity of 1.13-1.38 dl / g) for 10 minutes to obtain a premixed powder; the hot melt extruder temperature was set to 140°C and the screw speed was set to 20 r / min, and the premixed powder was added after preheating to the set temperature. After the timing was started for 20 minutes, it was extruded through a 0.5 mm diameter die, and the implant with a length of 50-150 cm in the middle was collected.
[0079] Implants with a cut length of about 7 mm were placed at 37±0.5°C in 4 mL of 0.01 M (pH 7.4) PBS buffer containing 0.5% SDS for in vitro release. All release media were removed at fixed time points and replaced with an equal amount of fresh media. The drug content in the release media was determined using an ultra-high performance liquid chromatograph, and the cumulative release percentage of the theoretical content was calculated.
[0080] The in vitro release of the obtained implants was as follows Figure 7 As shown by Figure 7 It can be seen that the implant has a certain sustained-release effect, and the in vitro release time can reach more than 10 days.
[0081] Example 12
[0082] The ideal release behavior requires not only long-term sustained release, but also a shortened release plateau period, wherein the in vitro release behavior of the implant described in Example 10 meets the requirements. The implant described in Example 10 at 0, 1, 3, 7 and 14 days of in vitro release was observed by scanning electron microscopy, and the in vitro release curve was fitted with the zero-order equation, the first-order equation, the Higuchi equation and the Ritger-Peppas equation using Origin2022Pro software to explain the release mechanism.
[0083] The results are as follows Figure 8 As shown, the in vitro release curve of the implant described in Example 10, the fitting coefficients R of the zero-order equation, the first-order equation, the Higuchi equation and the Ritger-Peppas equation are 0.9888, 0.9871, 0.9381 and 0.9876, respectively, indicating that its in vitro release mechanism can be explained by the zero-order release equation; the release characteristic index n = 1.01>1, combined with Fig. 9 The results of scanning electron microscopy at different time points of in vitro release showed that the drug release from the implant was mainly controlled by the dissolution and degradation of the water-insoluble biodegradable sustained-release polymer.
Claims
1. A method for preparing a high-drug-loaded anti-VEGF intraocular sustained-release implant, characterized in that: The following steps are involved: (1) crushing and sieving the anti-VEGF active ingredient to obtain an average particle size within a range of 70 to 125 μm; (2) crushing and sieving the water-insoluble biodegradable sustained-release polymer to a mean particle size within a range of 70 to 125 μm; (3) mixing the crushed and sieved anti-VEGF active ingredient and the water-insoluble biodegradable sustained-release polymer evenly to obtain a premixed powder; (4) Setting the temperature of the hot melt extruder to 90-150° C., setting the screw speed to 15-30 r / min, and installing a 0.3-1.0 mm diameter die; (5) After the hot melt extruder is preheated to the set temperature, the premixed powder of step (3) is fed into the feed port, and the timing is started after all the powder enters the machine; (6) After timing for 5 to 30 minutes, start extrusion.
2. The preparation method according to claim 1, characterized in that: The anti-VEGF active ingredient in step (1) is one or a combination of two or more of nintedanib ethanesulfonate, nintedanib and voronib.
3. The preparation method according to claim 1, characterized in that: The water-insoluble biodegradable sustained-release polymer described in step (2) is one or a combination of two or more of polylactic acid, polylactic acid-glycolic acid copolymer, and polycaprolactone.
4. The preparation method according to claim 3, characterized in that: The polylactic acid is one of acid-terminated and ester-terminated, and the intrinsic viscosity of the polylactic acid is one of 0.16-0.24 dl / g, 0.25-0.35 dl / g and 0.80-1.20 dl / g; The polylactic acid-glycolic acid copolymer is one of acid-terminated and ester-terminated; the intrinsic viscosity of the polylactic acid-glycolic acid copolymer is 0.16-0.24 dl / g or 0.70-0.90 dl / g; the molar ratio of lactic acid to glycolic acid in the polylactic acid-glycolic acid copolymer is 75:25 or 50:50; the intrinsic viscosity of the polycaprolactone is 1.13-1.38 dl / g.
5. The preparation method according to claim 1, characterized in that: In step (3), the mass ratio of the anti-VEGF active ingredient to the water-insoluble biodegradable sustained-release polymer is 4:6 to 7:3, preferably 5:5 to 6:
4.
6. The preparation method according to claim 1, characterized in that: The mixing time in step (3) is 5 to 30 minutes, preferably 8 to 12 minutes.
7. The preparation method according to claim 1, characterized in that: The temperature of the hot melt extruder in step (4) is set to 100-140° C., preferably 120-140° C.; the screw speed is 15-25 r / min, preferably 17-23 r / min; and the mold diameter is 0.3-0.7 mm, preferably 0.4-0.6 mm.
8. The preparation method according to claim 1, characterized in that: The time in step (6) is 10 to 30 minutes, preferably 15 to 25 minutes.
9. The anti-VEGF intraocular sustained-release implant prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation of implant
CN111714442A
Axitinib intraocular implant
CN114533648A
Coated implants for long-term controlled release of antibody therapeutics
US20190151237A1
Ocular implant containing an active ingredient
US20230285282A1
Pharmaceutical formulations of nintedanib for intraocular use
US20240058264A1
Cited By
Nintedanib inhalation dry powder as well as preparation method and application thereof
CN120837461A